Non-invasive Loading Model of Murine Osteoarthritis - Poulet, Blandine (Curr Rheumatol Rep, 2016)
Osteoarthritis is the commonest degenerative joint disease, leading to joint pain and disability. The mouse has been the primary animal used for research, due to its size, relatively short lifespan, and the availability of genetically modified animals. Importantly, they show pathogenesis similar to osteoarthritis in humans. Mechanical loading is a major risk factor for osteoarthritis, and various mouse models have been developed to study the role and effects of mechanics on health and disease in various joints. This review describes the main mouse models used to non-invasively apply mechanical loads on joints. Most of the mouse models of osteoarthritis target the knee, including repetitive loading and joint injury such as ligament rupture, but a few studies have also characterised models for elbow, temporomandibular joint, and whole-body vibration spinal loading. These models are a great opportunity to dissect the influences of various types of mechanical input on joint health and disease.